Faktor-Faktor Yang Berhubungan Dengan Gangguan Fungsi Paru Pada Pekerja Pengelasan di Kota Pontianak - Deviandhoko, Deviandhoko; Wahyuningsih, Nur Endah; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2012)
Background: Home industry has grown rapidly in recent years in the Pontianak city. One of the exhaust particulatematerial from the welding process. This will be the potential occurrence of exposure to workers. Result from thispreliminary study (15 workers), found that the average work for 8-9 hours per day, taking hours of overtime (40,%)for 4 hours / day, and the symptom for respiratory disorders were cough (60%) and shortness of breath (20%), thisstudy showed that welding work had a risk of pulmonary function disorders for workers. The aim of this study was tomeasure lung function disorders in welding workers and factors influencing it in the Pontianak city.Methode: This research was an observational research using a cross sectional design, with 78 samples of workerwere taken by random sampling. Data of levels welding respirable dust were obtained by measured usingpersonal dust sampler, while lung function data obtained with examine the lung function of workers usingspirometri, and other data obtained by interview. Data analysis performed by univariate and biavariate analysisusing Kendall-tau and chi-square (Â±=0,05).Result : Study showed respirable dust still below threshold limit value (NAB=3 mg/m3), the highest = 2,791 mg/m3, the lowest = 0,085 mg/m3, mean= 0,83 mg/m3 and SD=0,70, and as many as 59 respondents (75.6%) hadpulmonary function disorders. Statistical test results showed there was significant association between level ofrespirable dust (p-value=0,001), and working hour/day (p-value=0,008, OR=6,321, 95%CI =1,663-24,026with pulmonary function disorders.Conclusion : Levels of respirable dust and duration of exposure is a potential factor of pulmonary functiondisorders in welding workers in the Pontianak city.Key words : respirable dust, capacity of lung function, welding workers, Pontianak.